Impact of seasonal changes on animal community structure (Zoological Records and Reviews, 2024)
Seasonal variation in temperature, precipitation, and resource availability drives predictable temporal fluctuations inanimal community structure across terrestrial and aquatic ecosystems. This study quantified seasonal shifts in speciesrichness, abundance, diversity indices, and guild composition across four animal communities -- ground-dwelling beetles(Coleoptera: Carabidae), breeding birds, stream macroinvertebrates, and small mammals -- sampled monthly across fourseasons at three paired land-use sites (semi-natural grassland, managed cropland, riparian woodland) in northern Italyand central Austria between January 2022 and December 2023 (n = 14,832 individual records across 284 taxa). Speciesrichness peaked in summer across all four groups (mean increase over winter baseline: +68.4% for carabids, +112.3%for birds, +44.1% for macroinvertebrates, +38.7% for small mammals). Shannon diversity (H') showed the strongestseasonal signal in breeding birds (summer H' = 2.84 +- 0.18 vs. winter H' = 1.31 +- 0.14; paired t(8) = 11.42, p < 0.001).Multivariate community composition (NMDS on Bray-Curtis dissimilarity) revealed significant season x land-useinteraction effects for all four groups (PERMANOVA F >= 3.8, p
Keywords: land-use effects; PERMANOVA; NMDS; small mammals; macroinvertebrates; breeding birds; Carabidae; Shannon diversity; species richness; seasonal community dynamics